Geochemistry and petrogenesis of post-collisional alkaline and peralkaline granites of the Arabian-Nubian Shield: a case study from the southern tip of Sinai Peninsula, Egypt. Issue 8 (11th June 2018) - Khalil, A. E. S.; Obeid, M. A.; Azer, M. K.; Asimow, P. D.
ABSTRACT: The southern Sinai Peninsula, underlain by the northernmost extension of the Arabian-Nubian Shield, exposes post-collisional calc-alkaline and alkaline granites that represent the youngest phase of late Neoproterozoic igneous activity. We report a petrographic, mineralogical and geochemical investigation of post-collisional plutons of alkaline and, in some cases, peralkaline granite. These granites intrude metamorphosed country rocks as well as syn- and post-collisional calc-alkaline granitoids. The alkaline and peralkaline granites of the southern tip of Sinai divide into three subgroups: syenogranite, alkali feldspar granite and riebeckite granite. The rocks of these subgroups essentially consist of alkali feldspar and quartz with variable amounts of plagioclase and mafic minerals. The syenogranite and alkali feldspar granite contain small amounts of calcic amphibole and biotite, often less than 3%, while the riebeckite granite is distinguished by sodic amphibole (5–10%). These plutons have geochemical signatures typical of post-collisional A-type granites and were most likely emplaced during a transition between orogenic and anorogenic settings. The parental mafic magma may be linked to lithospheric delamination and upwelling of asthenospheric mantle material. Differentiation of the underplated basaltic magma with contributions from the juvenile crust eventually yielded the post-collisional alkaline granites. Petrogenetic modelling of the studied granitic suite shows that pure fractional crystallization cannot quantitatively explain chemical variations with the observed suite, with both major oxides and several trace elements displaying trends opposite to those required by the equilibrium phase assemblage. Instead, we show that compositional variation from syenogranite through alkali feldspar granite to riebeckite granite is dominated by mixing between a low-SiO2 liquid as primitive or more primitive than the lowest-SiO2 syenogranite and an evolved, high-SiO2 liquid that might be a high-degree partial melt of lower crust.